Transcriptional regulation of macrophages in heart failure - Wang, Keyan; Sun, Xiaoqian; Sun, Ying; Jiao, Boyang; Yao, Junkai; Hu, Yueyao; Deng, Qiong; Dong, Jianteng; Wang, Wei; Wang, Yong; Li, Chun (Frontiers in Cardiovascular Medicine, 2023)
Adverse cardiac remodeling after acute myocardial infarction is the most important pathological mechanism of heart failure, and still a major problem in clinical practice. Cardiac macrophages, derived from tissue resident macrophages and circulating monocyte, undergo significant phenotypic and functional changes following cardiac injury, and play crucial roles in the inflammatory response and the tissue repair response. Currently numerous studies indicated that epigenetic regulatory factors and transcription factors can regulate the transcription of inflammatory and reparative genes, timely conversion of inflammatory macrophages into reparative macrophages, and then alleviating cardiac remodeling. Accordingly, targeting transcriptional regulation of macrophages may be a promising target for the heart failure treatment. In this review, we not only summary the origin and function of cardiac macrophages, more importantly, described transcriptional regulation of macrophages in heart failure, aimed to provide a potential therapeutic target for heart failure.